Mischief, Mystery, and Moments That Matter: Vistas of Performative Inquiry. (February 2014) - Gergen, Kenneth J.; Gergen, Mary M.
Here we challenge the traditional separation of science and art and demonstrate significant ways in which the social sciences can be enriched through performative inquiry. We begin with a brief commentary on philosophic work that detaches representation from observation. In effect, there is no privileged (in principal, accurate, neutral, or objective) representation of a given observation. We then explore the potentials of expanding the repertoire of representation to include forms more traditionally located within the arts. Included are instances of experimental writing, performative monologue, autoethnography as poetry; dramatic performance and visual art as theory. By expanding the repertoire of inquiry in this way, not only are the social sciences enriched but also their capacity to communicate with the surrounding culture.